Progress in injectable hydrogels for the treatment of incompressible bleeding: an update - Wang, Xiudan; Yang, Xinran; Sun, Zhiguang; Guo, Xiaoqin; Teng, Yanjiao; Hou, Shike; Shi, Jie; Lv, Qi (Frontiers in Bioengineering and Biotechnology, 2024)
Uncontrollable haemorrhage from deep, noncompressible wounds remains a persistent and intractable challenge, accounting for a very high proportion of deaths in both war and disaster situations. Recently, injectable hydrogels have been increasingly studied as potential haemostatic materials, highlighting their enormous potential for the management of noncompressible haemorrhages. In this review, we summarize haemostatic mechanisms, commonly used clinical haemostatic methods, and the research progress on injectable haemostatic hydrogels. We emphasize the current status of injectable hydrogels as haemostatic materials, including their physical and chemical properties, design strategy, haemostatic mechanisms, and application in various types of wounds. We discuss the advantages and disadvantages of injectable hydrogels as haemostatic materials, as well as the opportunities and challenges involved. Finally, we propose cutting-edge research avenues to address these challenges and opportunities, including the combination of injectable hydrogels with advanced materials and innovative strategies to increase their biocompatibility and tune their degradation profile. Surface modifications for promoting cell adhesion and proliferation, as well as the delivery of growth factors or other biologics for optimal wound healing, are also suggested. We believe that this paper will inform researchers about the current status of the use of injectable haemostatic hydrogels for noncompressible haemorrhage and spark new ideas for those striving to propel this field forward.